The systemwide livestock programme: A promising research-for development concept - Smith, Jimmy W.; Keatinge, J.D.H.; Smalley, M.E.; Quiróz, R. (International Livestock Research Institute, 2004)
Expansion of global population each year at the rate of approximately 90 million more than the current population of The Philippines will also necessitate unprecedented expansion of food production. As there is little room to bring more land under cultivation, almost all of the increase must come from productivity gains. The challenge being faced is much more complex than ever before, as never before have agricultural systems had to respond simultaneously to the triple goals of increasing food security, reducing rural and global poverty, and improving the management of natural resources. As with earlier challenges science is being looked upon to provide the solutions. New kinds of scientific partnerships will be required to respond to this triple challenge. Such partnerships must facilitate strong alliances among the international agricultural research centres of the Consultative Group on International Agricultural Research (CGIAR), advanced research institutions in both developed and developing countries, and the national agricultural research systems of developing countries. These partnerships must lever the intellectual and material resources of their members, promote coherence and capitalise on synergies. The Systemwide Livestock Programme (SLP) of the CGIAR is offered as one such partnership model. How this Programme responds to the aforementioned challenges and its use of virtual networks and virtual laboratories to facilitate decentralised management, promote ownership and provide operational effectiveness and efficiencies within global partnerships are discussed in this paper.